From cyborg feminism to drone feminism: Remembering women's anti-nuclear activisms. (December 2015) - Feigenbaum, Anna
By the 1990s the dynamic array of creative direct action tactics used against militarised technologies that emerged from women's anti-nuclear protest camps in the 1980s became largely eclipsed by cyberfeminism's focus on digital and online technologies. Yet recently, as robots and algorithms are put forward as the vanguards of new drone execution regimes, some are wondering if now is the time for another Greenham Common. In this article I return to cyborg feminism and anti-nuclear activisms of the 1980s to explore what drone feminism might look like today. I examine how anti-nuclear protesters infused affect and techné, creating innovative images of, and tactics for, material resistance. I argue that Greenham women's cyborg feminisms arose from their material entanglements with the military base. In their efforts to reveal and undermine the national and imperial myths upon which warfare is based, protesters re-imagined technological possibilities based upon a global accountability for 'earthly survival'.